The Need for a Breakthrough: A Dialogical Approach to the Situation of Faith Today. - Skorulski, Krzysztof (Filozofia Chrześcijańska, 2012)
The „Tischner-Days” Symposium of 2010 examined the topic: „The World and Faith in a Time of Breakthrough”. The newly published conference papers try to define the situation of culture and faith in western civilisation today. The Symposium participants concentrated their efforts mostly on such terms as „individualisation”, „secularisation” and the „holy”. In this article we try to re- read these terms as the description of ongoing changes in the context of Ferdinand Ebners’ dialogical view of the person. Our attempt is therefore to evaluate whether the processes result in a more personal (inter-personal) world or, rather, in a new ideology, experienced in „I-aloneness” (Ebner). Individualisation – the key term of our analysis – could signify a positive process (as for example K. Popper suggests), when it truly leads from collectivism with its ideology to individualism understood as a (dialogical) person (as in Ebner, Guardini or Mounier). Currently secularisation (Ch. Taylor, K. Gabriel) stands in opposition to Max Webers’ old „secularisation thesis” of pluralisation according to the individual situation of the person, rather than the disappearance of faith. The changes in the sphere of the „holy” could be positive if seen as focusing on the „I-Thou” relation. However, when the ongoing individualisation is not grounded in a dialogical view of the person, it can end up merely as a shift from one ideology to another; secularisation could end up merely as the dissipation of consciousness in a superficial and impersonal „vision”, and the experience of God could become impersonal as mere energy or radiation. When the real life of the person must be seen in terms of his real „spirit”, we are, instead, dealing here with a „dream of the spirit” – as Ebner says. What then is to be done? To make our times more human (so the humanity of the person will subsist in the dialogical dimension), the „need for a breakthrough” becomes urgent. We should not only foster the interpersonal dialogue, but also fight against „structural loneliness”, i.e. to convert abstract (inhumane) notions into human (dialogical) notions (for example as D. Graebers’ attempts with „debt”).